(untitled) (International Journal of Physiotherapy, 2023)
Background: Neuro-physiological conflict between reciprocal inhibition and nonreciprocal inhibition phenomena during electrical stimulation of spastic muscles may give scope for new technological advances in electrical stimulation techniques for spasticity reduction. This study compares the effects of antagonistic motor point stimulation and agonist stimulation at muscle–tendon junctions on biceps spasticity. Methods: 11 post-stroke patients between 40 and 60 years of age were randomly assigned to two groups. In the antagonist-stimulation group, electrical stimulation is given to the triceps muscles, up to 30 contractions in a single session with the frequency of 40 Hz-100Hz and 0.7ms pulse duration. In the agonist-stimulation group, the patient’s musculotendinous junction of spastic biceps is marked with the help of diagnostic ultrasound before starting the treatment. Spastic biceps was stimulated at the musculotendinous junction up to 30 contractions in a single session with a frequency of 40Hz to 70Hz and 0.7ms pulse duration. Both groups received single-treatment sessions per day for five days a week for four weeks. Stretch pain on VAS and ENMG (H reflex and F/M ratio) were recorded on the first day and after four weeks of treatment. Results: Extremely significant reduction in spasticity (p=<0.0001) and stretch pain (p=<0.0001) were noted after both types of stimulations. Subjects in the agonistic stimulation group showed significant improvement in both outcome measures compared to the antagonistic stimulation group, with a mean difference of 2.965ms in H reflex and 1.235 in F/M ratio. More significant improvement in pain was noted in the agonistic stimulation group (p=0.0002). These results demonstrated a significant spasticity reduction in agonistic stimulation compared to agonistic stimulation. Conclusion: Agonist stimulation at a musculotendinous junction is more effective than antagonistic stimulation at a motor point in reducing spasticity in MCA stroke subjects.